Monetary Trends in the United States and the United Kingdom: A Review from the Perspective of New Developments in Monetary Economics - Hall, Robert E. (Journal of Economic Literature, 1982)
MILTON FRIEDMAN AND ANNA SCHWARTZ Monetary Trends reports a great many findings-53 are enumerated in the introduction-but paramount is the stability of the demand for money in the US and Britain over the past century. The money stock controls money income. This proposition more than anything else is the point of their painstaking investigation. Friedman and Schwartz argue against what might neutrally be called the early post-war view of the macroeconomic role of money: Velocity will move easily to reconcile any level of nominal income to any money stock. The demand for money in this view is a will-o'the-wisp, as the authors put it. Monetary policy has little influence over real activity; stabilization policy necessarily relies on fiscal instruments. The volume is completely convincing in disposing of this idea; today's reader is likely to be puzzled why so much space is devoted to a view that has no serious adherents among professional economists. Friedman and Schwartz are generals fighting an earlier war, a situation accentuated by the long lags in putting this volume into print. Though the opposing armies fighting for the early postwar view have withdrawn in total rout, a new front has opened up, and the quantity theory is fighting for its life once again. Worse yet, the new armies are fighting under the banner of free-market economics and are led by former colleagues and students of Milton Friedman. The midwest, once the stronghold of the quantity theory, is now largely occupied by the enemy. The new monetary economics views the quantity theory as nothing more than an artifact of government regulation. An economy organized along free-market principles could function without money at all (Fischer Black, 1970). It is true that the kinds of monetary regulations imposed by the American and British governments of the past century create a more-or-less stable relation between a certain class of assets called money and nominal spending (Eugene Fama, 1980), but different regulations would alter that relation. Even the real bills doctrine, anathema to quantity theorists because it invites unlimited expansion of the money supply, has advocates in the new school (Thomas Sargent and Neil Wallace, 1981). monetary system where the government is unconcerned about the money stock has been advocated by a University of Chicago economist while visiting the Hoover Institution (John Bilson, 1981). Restoring the intrinsic value of money, not limiting its quantity, has been found to be the key to successful disinflation by one member of this group (Sargent, 1982). critical summary, titled A Laissez Faire Approach to Monetary Stability, written * See p. 1528, above, for publication information.